Profile of Medico-legal Age Estimation Cases in a Tertiary Hospital in Kathmandu - Chaudhary, Gopal Kumar; Shrestha, Sabnam; Dahal, Samarika; Maharjan, Mani Raj; Walung, Eugen Dolma; Kadel, Tulsi; N, Srikant (Nepal Journal of Health Sciences, 2024)
Introduction: Medico-legal age estimation is the estimation of chronological age of an individual which is based upon analysis of physical development of the body, development of secondary sexual traits, tooth eruption, appearance of ossification centers of bones, and the degree of epiphyseal union. Chronological age of the subject whether a minor (less than 18 years) or an adult determines the fate of the case in the court of law. Objective: The present study revealed varied profiles of the perpetrator and the victim who came for medico-legal age estimation. Methods: This is a retrospective, descriptive cross-sectional study conducted in the Department of Forensic Medicine, Maharajgunj Medical Campus, Institute of Medicine (IoM). The data of medico-legal age estimation of 5 years period was analyzed using the statistical software SPSS 20. Results: Total of 313 individuals were studied. Majority of the individuals were within the age group of 16-17 years. Males (70.3 %) outnumbered females (29.7 %). Theft (31.9 %) was common among subjects, followed by sexual assault (18.2 %) and majority of subjects (59.7%) came from Province 3. Sixty percent of the subject’s alleged age, matched the estimated ages. Conclusion: This study shows the status of children in crime which demands attention of concerned authority. Males were significantly involved in theft and females were victims of sexual assault. Forty percent of the alleged age given by the subject differed from the estimated age, to change the fate of the case. These results could greatly benefit the judiciary system of Nepal.